ANALISIS KEPUTUSAN PEMBELIAN KONSUMEN MOTOR SUZUKI DI DKI JAKARTA - Sapto Eka Prasetya, (2024)
This research is a quantitative study that aims to determine the effect of product quality, brand image and promotion on consumer purchasing decisions for Suzuki motorbikes. The population and sample in this study are Suzuki motorcycle consumers who live in the DKI Jakarta area and participate in the Suzuki motorcycle purchasing decision process and Suzuki motorcycle consumers who are more than 17 years old. The sample method used in this study is purposive sampling method in accordance with certain criteria and the sample set in this study amounted to 100. Hypothesis testing using bootstrapping and data processed using SmartPLS version 3.2.8 software. Based on the hypothesis test generated after data processing, namely (1) product quality has a positive and significant effect on purchasing decisions, (2) brand image has a positive and significant effect on purchasing decisions, (3) promotion has a positive and significant effect on purchasing decisions.